Efecto del bienestar psicológico en el desempeño laboral del personal administrativo de la ESPAM MFL - Rivas Montesdeoca, Omaira Carolina (2024)
This study, aimed at the administrative staff at ESPAM MFL, sought to understand the connection between psychological well-being and job performance. Specific objectives included a detailed analysis of the current situation related to psychological issues among administrative personnel, achieved through research in scientific and academic articles, as well as the consultation of information in ESPAM MFL's internal documents. A methodology was designed to fulfill these objectives, initiating with an analysis of the current situation through a review of scientific literature and the collection of internal data. Subsequently, the correlation between the study variables was established, developing a robust database structure. The determination of the relationship between variables was approached systematically through a data analysis process. The results revealed a moderate positive correlation between psychological well-being and job performance, based on data collected from 108 administrative workers. This connection suggests that higher psychological well-being is associated with an increase in job performance. Statistical significance supports the validity of this relationship, indicating it is not random, and a real connection exists between psychological well-being and job performance. These findings reinforce the importance of promoting psychological well-being as an effective strategy for enhancing job performance in the organizational context. Concurrently, a strategic plan was developed to strengthen the psychological well-being of administrative staff.